Two translations of Franz Kafka's short story "Die Verwandlung": a stylistic analysis and comparison. - Czakan, Patricia (My University, 1994)
This research project focuses on two English translations of Franz Kafka's short story "Die Verwandlung". (Abbreviation abstract)
A translation research project submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Translation.
Keywords: KAFKA, FRANZ, 1883-1924. VERWANDLUNG.; KAFKA, FRANZ, 1883-1924--TRANSLATIONS.; TRANSLATING AND INTERPRETING.